Risk Management in Implementation City Road Project in Padang City - Putra, Rifano; Ophiyandri, Taufika; Hidayat, Benny (CIVED, 2024)
Risks can have an impact on the productivity, performance, quality and cost limits of a project and risks can be said to be consequences that may occur unexpectedly. The success of a construction project really depends on the ability of project management to manage the risks that occur. The role of transportation in the city of Padang is to support the economic, education, tourism and defense and security sectors. Construction projects are a dynamic field and contain risks. The aim of this research is to identify risks and carry out risk analysis in the implementation of city road construction projects in the city of Padang as well as carry out risk responses for risk ownership in order to reduce the consequences caused by these risks. This research uses primary and secondary data which will later become a questionnaire and conduct interviews. Questionnaires were distributed to respondents, namely contractors, the results of the questionnaire calculation analysis using the Severity Index (SI) method from during the implementation of urban road construction in the city of Padang, 47 (forty seven) risks were identified based on activities at the project implementation stage. The risks identified are 2 (two) political risks, 7 (seven) environmental risks, 2 (two) planning risks, 2 (two) marketing risks, 3 (three) economic risks, 1 (one) financial risk, 6 ( six) natural risks, 7 (seven) project risks, 7 (seven) technical risks, 2 (two) human risks, 3 (three) criminal risks and 5 (five) safety risks. Of the identified risks, an analysis of the level of risk acceptance was carried out which showed that there were 23 (twenty-three) risks that were included in the highest risk category or unacceptable risk category (Unacceptable) and 24 (twenty-four) risks that were included in the risk category. not expected (Undesirable). Ownership of the greatest risks is the responsibility of the contractor because during the project, the contractor has a central role as controlling the overall course of the project.